Analysis of User Satisfaction with LIVIN’ by Mandiri as User Feedback in the Domain of Continual Service Improvement - Talmi Gam; Rudi Latuperissa (SISTEMASI, 2026)
The rapid development of digital banking services necessitates continuous service quality improvement to ensure that user experiences remain aligned with evolving needs and expectations. This study aims to analyze user satisfaction with the Livin’ by Mandiri application and to identify priority areas for improvement using the ITIL framework within the Continual Service Improvement (CSI) domain. This research adopts a descriptive quantitative approach with purposive sampling, involving 100 active users. Data were collected through questionnaires and analyzed using validity and reliability tests with the assistance of SPSS. The results indicate that the research instrument demonstrates excellent reliability (Cronbach’s Alpha = 0.934), and all questionnaire items are valid. The key Findings identify four factors influencing user satisfaction: interface design, reliability, responsiveness, and personalization. In addition, items X3.6 and X4.4 exhibit the lowest correlation values, indicating that they should be prioritized for improvement. From the CSI perspective, although the service demonstrates good quality and maturity, continuous improvement efforts are still necessary. These efforts should be carried out through iterative cycles of data collection, gap analysis, implementation of improvements, and evaluation to ensure sustained enhancement of service quality.